2020
DOI: 10.33019/lire.v4i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Level in English Speaking Among Ahmad Dahlan Students

Abstract: One language that is a communication tool in various parts of the world is English; English has become a language that must be mastered by the community, especially students. However, not everyone can easily speak English. The purpose of this research is to know the level of anxiety when they speak in English at Universitas Ahmad Dahlan students. This research uses a qualitative method. One hundred and twenty seven students were selected as the participants of the questionnaire; the tool used for this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Based on the results of the research and the results of the data analysis above, it shows that the hypothesis is accepted so that "there is a positive and significant relationship between low self-esteem and anxiety speaking English. This is also supported by the results of research by Basri (2019) which found factors that cause students' anxiety when speaking English are influenced by lack of confidence and fear of making mistakes.…”
Section: Journal Of Health and Behavioral Sciencesupporting
confidence: 56%
“…Based on the results of the research and the results of the data analysis above, it shows that the hypothesis is accepted so that "there is a positive and significant relationship between low self-esteem and anxiety speaking English. This is also supported by the results of research by Basri (2019) which found factors that cause students' anxiety when speaking English are influenced by lack of confidence and fear of making mistakes.…”
Section: Journal Of Health and Behavioral Sciencesupporting
confidence: 56%